Reflective Full Subcategories of the Category of L-Posets - Hongping Liu; Qingguo Li; Xiangnan Zhou (Abstract and Applied Analysis)
This paper focuses on the relationship between L-posets and complete L-lattices from the categorical view. By considering a special class of fuzzy closure operators, we prove that the category of complete L-lattices is a reflective full subcategory of the category of L-posets with appropriate morphisms. Moreover, we characterize the Dedekind-MacNeille completions of L-posets and provide an equivalent description for them.